PENGARUH KEGIATAN KEAGAMAAN DAN MOTIVASI TERHADAP PENGEMBANGAN RELIGIOSITAS SISWA KELAS VIII DI SEKOLAH MENENGAH PERTAMA SWASTA (SMPS) VIDYA SASANA KABUPATEN KARIMUN - Rubiyati, Rubiyati; Partono, Partono; Budi Utomo (LPSDI Bina Patria, 2024)
This indicates a moral crisis in society. This moral crisis is caused by low religiosity in children. This condition is in sharp contrast to the religious atmosphere and personality of the Indonesian nation. Low religiosity will weaken the values ​​of national and state life. Responding to the problems that occur as a result of the low level of religiosity among children and adolescents, educational institutions, especially secondary education, need to develop religious values ​​by organizing all components of education with indicators of internalized religious values ​​in students by increasing religious activities. thus motivating students to behave in accordance with religious values ​​in everyday life both in the family, at school, and in wider association in society. The author conducted this research with the aim of knowing the magnitude of the influence of religious activities and motivation on the development of students' religiosity either partially or simultaneously. The respondents for this research consisted of 36 class VIII students at SMPS Vidya Sasana Karimun. The data analysis technique used in this research is descriptive statistical techniques and parametric inferential statistics, and uses SPSS 25.00. Based on the results of this research, it can be concluded that simultaneously religious activities and student motivation have a positive and significant effect on the religiosity of class VIII students at SMPS Vidya Sasana